KALIMAT IMPERATIF DALAM FILM SPY KARYA PAUL FEIG SUATU ANALISIS SINTAKSIS - WENZEN, NOVITA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2016)
ABSTRACT This research entitled The Imperative Sentences in Spy Movie by Paul Feig. The objectives of this research are to identify, to classify the imperative forms and to analyze the function of imperative sentences. This research used descriptive method. The writer collected the data of imperative sentences from the script of â€œSpyâ€ Movie by Paul Feig. After collecting the data, the writer classified forms of imperative sentences by using theory from Quirk and Greenbaum (1973) then analyzed functions of imperative sentences according to the concept of Aarts and Aarts (1982). The result of this research shows that there are 250 imperative sentences found in â€œSpyâ€ movie by Paul Feig. The forms of imperative sentences consist of imperative sentences which are formed of : Commands without a subject (169), Commands with a subject (32), Commands with let (26), Negative imperative (23), Persuasive imperative is not found in this research. The functions of imperative sentences which are: Command (98), Wish (50), Invitation (26), Warning (76). KEYWORDS: Imperative Sentences, Spy Movie, Syntactic Analysis.